Navigating dynamics of farm household livelihood vulnerability to climate-related risks in southern Ethiopia: An agroecology-based comparative analysis - Daniel Dalle; Yishak Gecho; Sisay Belay Bedeke (Cogent Food & Agriculture)
Ethiopia is frequently mentioned as a country that is extremely vulnerable to climate change. The country’s high vulnerability is mostly from its climate-sensitive agricultural sectors. However, changes in rural household livelihood vulnerability levels were detected across agro ecologic zones. Thus, this study aimed to investigate agro-ecological-based farm households’ livelihood vulnerability to climate change in Wolaita Zone, Southern Ethiopia. The study used LVI-IPCC in addition to the overall vulnerability index to quantify vulnerability factors in three selected agro-ecologies. In this study, both primary and secondary data were used. Primary data were acquired from 371 sampled households, as well as through a focus group discussion and key informant interviews. Secondary data, notably climatic data, was accessed for the years 1991 to 2022. Data on biophysical features were also collected and incorporated into indices. The study found significant variation in vulnerability factors among agro-ecological systems, with Kola agroecology being the most vulnerable (0.04) due to its high exposure (0.59) and sensitivity values (0.58), and low ability to adapt (0.52). Dega agroecology was the least vulnerable (0.48) due to its low exposure (0.46) and sensitivity (0.44). Woyna Dega agro-ecology had an intermediate score in all three factors. Based on our findings, we suggested that resilience-building adaption strategies were critical for reducing the vulnerability of smallholder farmers, and the plans should also take into account local conditions. It also advocates for more decisive policy measures to improve the community’s adaptive capacity and reduce its exposure level.